KEBEBASAN DAN KEMANDIRIAN HAKIM DALAM PARADIGMA HUKUM PEMILIHAN PENJATUHAN RESTITUSI PADAPERKARA PENGANIAYAAN DI INDONESIA - Nida Syafwani Nasution; Rosmalinda; Mahmud Mulyadi (Smart Education, 2026)
Regulations on restitution for victims of abuse in Indonesia are normatively available and reinforced through Supreme Court Regulation Number 1 of 2022. However, their implementation remains inconsistent, particularly in practice, such as at the Stabat Court, where judges tend not to optimally utilize their freedom and independence in imposing restitution and remain formalistic and cautious. This research applies a normative legal approach because, to address the formulated problem, the primary focus is on literature review or the use of secondary data. The normative legal approach places greater emphasis on the use of secondary data and identifies structural and cultural barriers, including a lack of coordination among law enforcement officials, difficulties in proving victims' losses, victims' low understanding of the right to restitution, and a judicial system that still emphasizes punishment of perpetrators rather than victim recovery. Restitution is a crucial instrument that serves not only as compensation but also as a means of comprehensive recovery. Therefore, strengthening its implementation and the active role of judges are necessary to achieve a more effective balance of justice between perpetrators and victims.